Determination of hexachlorocyclopentadiene in water by HS-SPME-GC-MS - YOU Xihua; SHI Jinghua; WANG Weili; CAO Fangfang; ZHANG Fengju; QIN Chenghua (Gongye shui chuli)
A headspace solid-phase microextraction gas chromatography-mass spectrometry(HS-SPME-GC-MS) method was established for the determination of hexachlorocyclopentadiene in water, with using headspace solid-phase microextraction injection, DB-1 chromatographic column separation, and gas chromatography/mass spectrometry detector detection. The effects of coating solid-phase extraction needles, inlet temperatures, solid-phase extraction conditions, salt effects on the determination were systematically investigated, and the method was validated under the optimal experimental conditions. The results showed that hexachlorocyclopentadiene exhibited good linearity with chromatographic peak area within the mass concentration range of 0.1-10 µg/L, with a correlation coefficient of 0.997 and a detection limit of 0.03 µg/L. The actual surface water and wastewater samples were measured, and the monitoring result of wastewater sample was 0.5 µg/L, while the monitoring result of surface water sample was not detected. The actual samples were spiked with 0.5 µg/L and 1.0 µg/L, respectively. The recovery rate was 70%-87%, and the relative standard deviation was 4.14%-13.9%(n=6). This method was simple to operate, did not use organic solvents for extraction, had good precision and high accuracy, which could be used for rapid determination of hexachlorocyclopentadiene in industrial wastewater and surface water.